Fungal-Host Interaction: Curcumin Modulates Proteolytic Enzyme Activity of Candida albicans and Inflammatory Host Response In Vitro. (15th August 2018) - Chen, Emily; Benso, Bruna; Seleem, Dalia; Ferreira, Luiz Eduardo Nunes; Pasetto, Silvana; Pardi, Vanessa; Murata, Ramiro Mendonça
Abstract : Current treatments for Candida albicans infection are limited due to the limited number of antifungal drugs available and the increase in antifungal resistance. Curcumin is used as a spice, food preservative, flavoring, and coloring agent that has been shown to have many pharmacological activities. Thus, this study evaluated the modulatory effects of curcumin on major virulence factors associated with the pathogenicity of C. albicans . The minimum inhibitory concentration (MIC) of curcumin against C. albicans (SC5314) was determined. Biofilm formation was quantified and the proteinase and phospholipase secretion was measured. The cytotoxicity was tested in oral fibroblast cells. A cocultured model was used to analyze the gene expression of proinflammatory cytokines (IL-1 β, IL-1 α, and IL-6) from host cells, as well SAP-1 and PLB-1 by RT-PCR. The MIC was between 6.25 and 12.5  µ M, and the activity of proteinase enzyme was significantly decreased in biofilms treated with curcumin. However, proteinase gene expression was not downregulated after curcumin treatment. Furthermore, gene expressions of host inflammatory response, IL-1 β and IL-1 α, were significantly downregulated after exposure to curcumin. In conclusion, curcumin exhibited antifungal activity against C. albicans and modulated the proteolytic enzyme activities without downregulating the gene expression. In host inflammatory response, curcumin downregulated IL-1 β and IL-1 α gene expression.